2016
DOI: 10.1097/sla.0000000000001487
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Glutamine-supplemented Parenteral Nutrition in Surgical ICU Patients

Abstract: Objective To determine whether glutamine (GLN)-supplemented parenteral nutrition (PN) improves clinical outcomes in surgical ICU (SICU) patients. Summary Background Data GLN requirements may increase with critical illness. GLN-supplemented PN may improve clinical outcomes in SICU patients, but data in patient subgroups are limited. Methods A parallel-group, multicenter, double blind, randomized, controlled clinical trial in adults after gastrointestinal, vascular, or cardiac surgery who required PN and SIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 63 publications
(89 reference statements)
1
38
2
3
Order By: Relevance
“…With consideration of systemic disturbances that could culminate in multiple organ failure, our AP model did not confirm this harmful effect, despite our parenteral infusion of high glutamine doses. The most recent multicentric trial showed that parenteral glutamine infusion did not change the mortality rate of patients in the surgical intensive care unit but also did not improve clinical outcomes [37]. In our study, the mortality rate was lower and death occurred later in animals in the glutamine group compared with the other groups, although these differences were not significant.…”
Section: Discussioncontrasting
confidence: 76%
“…With consideration of systemic disturbances that could culminate in multiple organ failure, our AP model did not confirm this harmful effect, despite our parenteral infusion of high glutamine doses. The most recent multicentric trial showed that parenteral glutamine infusion did not change the mortality rate of patients in the surgical intensive care unit but also did not improve clinical outcomes [37]. In our study, the mortality rate was lower and death occurred later in animals in the glutamine group compared with the other groups, although these differences were not significant.…”
Section: Discussioncontrasting
confidence: 76%
“…A recent clinical trial performed in the United States found that supplementation with parenteral GLN is safe but did not influence the clinical outcomes of the ICU patients. 37 Furthermore, a systematic review reported by Wischmeyer et al 38 concluded that parenteral GLN supplementation reduces hospital mortality and length of stay when administered following resolution of shock and multiorgan failure. In this study, midgrade sepsis was induced and antibiotic was used to control the infection.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of significant knowledge and consideration of the role of the intestinal microbiome to modify, and be modified by, foodstuffs as they pass through the intestinal bioreactor, surgeons have over the years attempted to modify the metabolic response to injury with nutrients. Failure to enhance recovery after surgery was witnessed, including trials of glutamine, branched‐chain amino acids, arginine and various fat emulsions. Viewing the gut as a mere conduit for nutrient absorption led to missteps and miscalculations that nutrients in their most elemental form could be delivered parenterally and would be sufficient to reprogramme the immune system to enhance recovery.…”
Section: Role Of Nutrition To Modify Recovery After Surgerymentioning
confidence: 99%